The determinants of private flood mitigation measures in Germany: Evidence from a nationwide survey - Daniel Osberghaus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Public flood protection cannot totally eliminate the risk of flooding. Hence, private mitigation measures which proactively protect homes from being flooded or reduce flood damage are an essential part of modern flood risk management. This study analyses private flood mitigation measures among German households. The dataset covers more than 6000 households from all parts of the country, including flood plains as well as areas which are typically not at a high risk of riverine flooding. The results suggest that the propensity to mitigate flood damage increases i.a. with past damage experience and damage expectations for the future. The latter effect can be interpreted as a 'climate adaptation signal' in the flood mitigation behaviour. All other factors remaining equal, a strong belief in a climate-change-induced increase of personal flood damage in the next decades induces an increase of the probability of flood mitigation by more than 10 percentage points. Moreover, strong evidence for moral hazard effects in the flood mitigation behaviour cannot be observed. Households expecting insurance coverage do not reduce their mitigation efforts. Likewise, the expectation of government relief payments hinders mitigation only for some groups of households.
urn:nbn:de:bsz:180-madoc-368636
Keywords: Q54; D81; R22; 330; Climate change; Adaptation; Flood mitigation; Moral hazard; Charity hazard; Germany